Counseling on Stunting Prevention by Increasing Local Food Security Leads to the Climate Village Program - Yulianti, Ika; Ariyanti, Ririn; Lewuk, Maria Ulfanti Uhle; Noviani, Doris; Hidaya, Nurman (Borneo Community Health Service Journal, 2024)
Stunting is a growth disorder that generally occurs in children under five and the cases are increasingly worrying. Based on the results of the survey, the stunting rate in Nunukan Regency is the highest in North Kalimantan. Until now, the number of stunting cases in Nunukan has reached 1,101 children under five and spread across 21 villages. And one of the villages affected by stunting is Srinanti Village, Seimanggaris District. Seimanggaris can take advantage of the climatic village area where the strategy to be applied is in the form of planting tarp trees (Artocarpus odoratissimus) which have various health benefits and also a form of savings to increase the supply of tarap seed raw materials in the future for the processing of Sutarma innovation "Tarap Date Milk". Midwives as a dynamic profession must keep up with the development of this era, participate in developing themselves to participate in the global game, in the form of the active role of midwives in improving the quality of services, education and professional organizations with a commitment to refer to regulations. The purpose of the training is to increase the understanding of midwives who carry out the Independent Midwife Practice on the prevention and control of Covid-19 infection so as to limit direct deaths and avoid an increase in indirect deaths and maintain the quality of midwifery services from decreasing, as well as the rights of mothers and babies can still be fulfilled